2006
DOI: 10.1080/02678290500512227
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal director gliding at a strongly anchoring interface of polyimide

Abstract: A gliding of the director at the interface between a nematic liquid crystal and a solid medium is generally observed at many interfaces giving weak or moderately strong anchoring. This phenomenon is characterized by strongly non-linear dynamics and very long relaxation times (hours-days). The gliding of the director has also been observed very recently at the interface between a rubbed polyimide layer and a nematic liquid crystal which gives strong azimuthal anchoring. However, due to the weak nature of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 24 publications
(53 reference statements)
1
25
0
Order By: Relevance
“…Figures 3 and 4 are most typical with a50.44 when chisquared is minimized. This is similar to the findings of Faetti et al [1] for gliding from an external electric field and Faetti and Marianelli's [9] determination of a50.362. In comparing different sets of data, we used a value of a50.44, even when that value did not minimize chi-squared, because time constants can vary slightly with this exponent and changes in chi-squared were not significant.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Figures 3 and 4 are most typical with a50.44 when chisquared is minimized. This is similar to the findings of Faetti et al [1] for gliding from an external electric field and Faetti and Marianelli's [9] determination of a50.362. In comparing different sets of data, we used a value of a50.44, even when that value did not minimize chi-squared, because time constants can vary slightly with this exponent and changes in chi-squared were not significant.…”
Section: Resultssupporting
confidence: 88%
“…The slow regime, on the other hand, shows the surface director angle changing continuously without appearing to reach a stationary value. Most studies indicate that the slow dynamics associated with gliding can be characterized either by a stretched exponential [1,9] or a power law [5]. Another characteristic of gliding is that it is not only slow, but appears to be plastic; there is a memory effect [10].…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that the easy axis itself may slowly rotate under the action of strong (magnetic or electric) fields. Over the past few decades this slow motion -the socalled easy axis gliding -has received much attention * Email address: kiselev@iop.kiev.ua † Email address: eechigr@ust.hk as a widespread phenomenon observed in a variety of liquid crystals on amorphous glass [3], polymer [4][5][6][7][8][9][10][11][12][13] and solid [6,11] substrates. Recently, it was found that, in addition to magnetically (electrically) induced gliding, there is the photoinduced gliding of the easy axis in dye-doped liquid crystals [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Zenithal director gliding is observed as an electric field is applied perpendicular to the bounding plates [6] and after the applied electric field is removed [6,10]. By contrast, azimuthal gliding is observed as an electric field is applied parallel to the plates [12].…”
Section: Introductionmentioning
confidence: 98%
“…In the case of zenithal gliding we consider two sets of experiments, carried out by Joly et al [6] and Buluy et al [10], that focus on zenithal gliding in the presence of an electric field and after the electric field is turned off. In the case of azimuthal gliding, we consider the experiment carried out by Faetti & Marianelli [12], which provides evidence for azimuthal director gliding of a strongly anchored system as an electric field is applied across the layer. Zenithal director gliding is observed as an electric field is applied perpendicular to the bounding plates [6] and after the applied electric field is removed [6,10].…”
Section: Introductionmentioning
confidence: 99%